Energization of irrigation solution as a supplement in the cleaning and disinfection of the root channel system - Martinez, Andressa Loana (2022)
Endodontic treatment aims to control the microbial factor to ensure the maintenance of teeth in the oral cavity in the face of the diagnosis of a diseased condition. An unfavorable factor is the anatomical complexity of the root canal system, due to the presence of apical ramifications, accessory canals and isthmus, making it difficult to completely remove organic and inorganic remnants in these areas of difficult access during instrumentation. Seeking to improve this, during endodontic treatment, one of the tools used to combat microorganisms is the irrigating solution. Still, the use of these solutions is not sufficient to remove mineral material when used individually. Thus, the help of other agents and techniques is necessary for the best result. Passive ultrasonic irrigation is based on the principle that the passive insertion of a metallic tip/file attached to an ultrasonic device in a root canal filled with an irrigating or chelating solution, when activated, allows increasing the performance of the solution agitation and improving the removal of debris, smear layer and root canal filling materials. This work aimed to carry out a narrative review of the literature addressing the effectiveness of energizing the irrigating solution after the biomechanical process of the root canal system in different protocols. In general, the works presented in this literature review showed that the methods with agitation of the irrigating solution promoted better cleaning of the canal, the isthmus and removal of the smear layer in relation to the conventional method.